2010
DOI: 10.1007/s10930-010-9268-y
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms, Expression, Glycosylation, and Tissue Distribution of CTL2/SLC44A2

Abstract: Antibodies to the solute carrier protein, CTL2/SLC44A2, cause hearing loss in animals, are frequently found in autoimmune hearing loss patients, and are implicated in transfusion-related acute lung injury. We cloned a novel CTL2/SLC44A2 isoform (CTL2 P1) from inner ear and identified an alternate upstream promoter and exon 1a encoding a protein of 704 amino acids which differs in the first 10–12 amino acids from the known exon 1b isoform (CTL2 P2; 706 amino acids). The expression of these CTL2/SLC44A2 isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 28 publications
2
79
2
Order By: Relevance
“…The first CTL protein was isolated by screening a cDNA library from the Torpedo lobe, which is highly enriched in neurons to identify genes able to suppress the growth defects of a yeast mutant lacking choline transport and reduced choline metabolism 9,32 . Choline uptake experiments performed with CTL1 and CTL2 from different organisms using various heterologous cell systems showed that these CTL proteins can facilitate choline transport across membranes 9,[32][33][34][35][36] . To test whether CHER1 also has the capability to transport choline, uptake experiments were performed using Xenopus oocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The first CTL protein was isolated by screening a cDNA library from the Torpedo lobe, which is highly enriched in neurons to identify genes able to suppress the growth defects of a yeast mutant lacking choline transport and reduced choline metabolism 9,32 . Choline uptake experiments performed with CTL1 and CTL2 from different organisms using various heterologous cell systems showed that these CTL proteins can facilitate choline transport across membranes 9,[32][33][34][35][36] . To test whether CHER1 also has the capability to transport choline, uptake experiments were performed using Xenopus oocytes.…”
Section: Resultsmentioning
confidence: 99%
“…17 Among these tissues, lungs possess abundant amounts of CTL2 transcripts encoding for 2 different isoforms, CTL2-P1 and CTL2-P2. 35 Whereas the CTL2-P2 isoform exhibits choline transport activity, no function has been described for CTL2-P1 to date.…”
Section: Discussionmentioning
confidence: 99%
“…17 CTL2-P1 and CTL2-P2 differ in the first exon (exon 1a or exon 1b) that encodes for 10 to 12 amino acids ( Figure 1A, left). To analyze the presence of human CTL2-P1 and CTL2-P2 transcripts in endothelial cells and neutrophils, reverse transcription-polymerase chain reaction was established using specific forward primers, P1 or P2, and a universal reverse primer.…”
Section: Endothelial Cells Express P1 and P2 Isoforms Of Ctl2 And Reamentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of SLC44A1 protein in the rat and human central nervous systems, where it is found in neuronal, glial and endothelial cells, suggests that malfunction of this transporter may have important implications in nervous system development and repair following injury, and in neurodegenerative diseases (10). SLC44A2 is expressed as two isoforms, SLC44A2-P1 and SLC44A2-P2, in the heart, colon, lung, kidney and liver, which suggests that tissue-specific differences may influence its function in each tissue (11 is present in the kidney, ileum and colon, while a notably strong SLC44A4 expression can be detected in the intestine, stomach and kidney. Much fewer data are available regarding the expression of SLC44A5, which was markedly low in the brain and higher in the spinal cord, however, to a lesser extent than SLC44A1 (12).…”
Section: Introductionmentioning
confidence: 99%